The Interrelation Between Hirsutism and Androgen Hormone Levels as Well as Serum TNFΑ Concentrations - Berliana Agata Siregar; Sri Ekawati (Malahayati Nursing Journal, 2024)
ABSTRACT Hair growth is subject to numerous factors that influence the development of hair follicles, including conditions such as alopecia areata and hirsutism. Hirsutism, a medical term denoting the excessive growth of terminal (coarse) hair in areas of a woman's body sensitive to androgens, occurs in approximately 7% of reproductive-age women. The majority of hirsutism cases are attributed to androgen excess. Elevated androgen hormone levels can trigger inflammatory responses through an increase in serum TNFα. Data collection involved sourcing articles relevant to the association between hirsutism, androgen hormone levels, and serum TNFα. Inclusion criteria comprised original articles, case-control studies, and review papers focusing on hirsutism, androgen hormones, and serum TNFα. Hirsutism is correlated with both androgen hormone levels and serum TNFα. Hirsutism arises from the interplay between androgen levels and the sensitivity of hair follicles to androgens. Several conditions triggered by high concentrations of androgen hormones can lead to the occurrence of hirsutism. Androgen hormones induce inflammatory effects, as evidenced by the presence of TNFα. Keywords: Hirsutism, Androgen, TNFα